STRATEGIES USED BY TEACHERS IN MOTIVATING STUDENTS TO LEARN ENGLISH AT THE TENTH GRADE OF SMA NEGERI 2 LASALIMU - Tita Herlinda; La Dunifa; Nur Melansari (English Education Department, 2020)
The objective of this research is to find out the english teachers strategies to increase the students motivation in learning english. This research used descriptive qualitative research method. Sources of data in this research are the English teacher and the tenth grade students of SMA Negeri 2 Lasalimu. Instruments used in this research were observation and interview. In validating the data, the researcher used data source by comparing the result of observation and interview. This research is analyzed by using Miles and Huberman’s interactive model of data analysis including reducing the data, displaying the data and taking conclusion and verification. The result of the research showed that the strategies used by the teacher in motivating students to learn English at the tenth grade of SMA Negeri 2 lasalimu are giving praise, giving suggestion, and playing motivation videos. Because by this technique it can attract the attention of students in teaching, students do not get bored quickly, more enthusiasm in learning English and increase knowledge they have. The strategies to increase motivation given by the English teacher to the students were extrinsic motivation (based on the source of motivation) in teaching English as media to arouse students of reaching the goal.